Volume 5B: Oil and Gas Applications; Steam Turbines 2013
DOI: 10.1115/gt2013-94788
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady CFD Simulation of Control Valve in Throttling Conditions and Comparison With Experiments

Abstract: The operational flexibility of steam power plant is becoming more important as power generation becomes increasingly decentralized, with a growing contribution from renewable energy sources. In a power plant the control valve is a key component to guarantee the control of the plant of which is increasingly demanded to extend the operational capability. At specific operating conditions, the control valve could experience vibrations. In this paper, the physical phenomena of the unsteady aerodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This idea can be applied theoretically to any turbulence model, although most applications of the SAS principle are conducted on the basis of the k − ω SST model following the work of Menter and Egorov [14]. This work, based on the procedure proposed and validated by Zanazzi et al [7], exploits the k − ω SST SAS model in the version implemented within the commercial CFD code Anysys CFX v14. 5.…”
Section: Turbulence Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea can be applied theoretically to any turbulence model, although most applications of the SAS principle are conducted on the basis of the k − ω SST model following the work of Menter and Egorov [14]. This work, based on the procedure proposed and validated by Zanazzi et al [7], exploits the k − ω SST SAS model in the version implemented within the commercial CFD code Anysys CFX v14. 5.…”
Section: Turbulence Modelingmentioning
confidence: 99%
“…More recently Zanazzi et al [7] performed a numerical investigation of the unsteady behavior of a steam turbine partition valve in throttling conditions. This work compared a simplified in-house procedure with full 3-D Computational Fluid Dynamics (CFD) analysis and experiments available for a single seat valve with axisymmetric stem under a large number of working conditions characterized by five different unsteady modes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the experimental research, various numerical investigations were conducted on several different valve geometries. The fluid-structure interaction in the spherical valve design investigated by Morita et al (2004) was further investigated by Zanazzi et al (2013) using numerical methods. For a can shaped valve design several publications by Domnick et al (2014Domnick et al ( , 2015Domnick et al ( , 2016 discuss part load performance and resulting flow patterns and reaction forces, considering fluid-structure interaction effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unsteady flow behaviors inside the control valves have been investigated through high-fidelity numerical simulations such as scale-adaptive simulation (SAS), detached-eddy simulation (DES), and large-eddy simulation (LES). For traditional valves with a spherical spindle, Morita et al 13 performed LES on a scaled-down model, and they found that the unstable wall-detached flow induced a cyclic asymmetric side load to the valve spindle; the SAS of Zanazzi et al 14 showed that unstable wall-detached flow also resulted in severe shock-wave oscillations inside the downstream pipe. Subsequently, Yonezawa et al 15 conducted DESs with experimental validation for a cutoff control valve; their numerical results demonstrated that wall-detached flow introduced a rotating high-pressure region acting on the valve spindle, yielding a periodically fluctuating lateral force.…”
Section: Introductionmentioning
confidence: 99%